(untitled) (Applied Biological Research, 2014)
Cherry (Prunus avium L.), an important stone fruit of temperate zone, is grown on an area of 3,728 ha in Jammu & Kashmir State with an annual production of 11,122 metric tonnes (Anonymous, 2012). In June-July 2013, typical leaf spot symptoms, quite different from those caused by Cercospora and Stigmina pathogens, were noticed on cherry leaves from Bandipora, Baramulla and Srinagar districts in Kashmir. The disease symptoms initially manifested as small circular purple